Vegetation types and habitats with participation of plant species – local endemics to the marble part of Northern Pirin Mts., Bulgaria - Nacheva, Veradina; Tzonev, Rossen; Pachedjieva, Kalina; Kolchagov, Rumen; Gussev, Chavdar; Pavlova, Dolja (IOP conference series. Earth and environmental science, 2024)
This study was carried out in the carbonate (marble) part of North Pirin Mts. Its upper parts are declared protected area of National Park category according to the Bulgarian Protected Areas Act. It is also a NATURA 2000 protected zone under the Habitats Directive, and a natural UNESCO World Heritage Site. The main reason for the conservation of this territory is the exceptional concentration of rare, relict and endemic plant species, its specific flora, vegetation and fauna. Subject of the study are the plant communities and habitats, with participation of 8 local endemic plant taxa, such as Cyanus achtarovii, Oxytropis kozhuharovii, O. urumovii, Odontarrhena orbelica, Alyssum pirinicum, Veronica kellereri, Brassica nivalis subsp. jordanoffii and Arabis ferdinandi-coburgii . The plant communities were studied according to the classical Braun-Blanquet’s approach by sampling the phytocoenoses, where the local endemics participate. The major syntaxa to which these communities belong, were determined. The plant communities with the participation of local endemics were also referred to lower units according to EUNIS habitats classification. The study found that most of the studied endemic species occur in various vegetation types and exhibit relatively wide ecological flexibility, despite inhabiting restricted area. The main reason for this is the comparative uniformity of the high mountain marble relief. This study also highlights the high conservation value of the vegetation cover and habitat diversity of the carbonate alpine and subalpine vegetation belts of Northern Pirin Mts., as a habitat for numerous endemic and relict plant species.